Exploring behavioural responses of shorebirds to impulsive noise - Wright, Mark D; Goodman, Paul; Cameron, Tom C (Wildfowl, 2013)
Despite recent research interest in the consequences of chronic noise for animal populations, the effects of impulsive noise are less well understood. Determining wildlife responses to impulsive sound is pertinent in coastal areas where development of port and power generation industries may result in disturbance from impulsive sounds such as percussive piling, especially around estuaries which may support internationally important numbers of bird species. Discussions between regulators, planning authorities and regional development agencies over precautionary levels of impulsive sound emitting activities are common, yet weâ€™re unaware of any study which provides guidance on acceptable noise limits that would keep disturbance to shorebirds to a minimum. This experimental study intentionally disturbed birds at a high tide roost site, an agricultural field adjacent to the sea wall on the south bank of the Humber estuary in northern England, using an impulsive sound, and their behavioural responses were recorded. The researcher sounded an air-horn at ever decreasing distances towards a mixed species flock of shorebirds. While visual disturbance from the experimenter was taken into consideration in the methods, we cannot statistically separate their effects in this study. An ordinal logistic regression model demonstrated a statistically significant positive relationship between the decibel (dB(A)) level experienced by the birds and the behavioural response observed. In principle, this model can be used to predict the probability of a particular behavioural response at a given dB(A) level. Estimates of sound levels which included calculation of geometric and atmospheric attenuation were superior over more simple measures in predicting behavioural responses. This study has implications for assessing possible disturbance caused by impulsive noise, and addsÂ to growing evidence that the effects of noise may be an important, albeit not straightforward, consideration in management decisions made for shorebirds and other avian species.